Methicillin resistant Staphylococcus aureus: mecC gene and vancomycin susceptibility - Diaz, Raquel Catarina Saraiva (2018)
Staphylococcus aureus is a major cause of infection and vancomycin the gold standard for its treatment. In 2011, mecC gene was discovered in methicillinresistant Staphylococcus aureus, this gene shares 69% nucleotide homology with mecA gene. Also in recent years it has been described a phenomenon called "MIC creep", which describes the increase of the minimum inhibitory concentration of vancomycin within susceptibility range. The aims of this work included the evaluation of the overall prevalence of mecC gene and the worldwide phenomenon of “MIC creep” using meta-analysis techniques. Since that in Portugal this investigation is still residual and because this is a phenomenon with regional characteristics, it was also assessed the presence of “MIC creep” in Staphylococcus aureus strains of Centro Hospitalar Baixo Vouga, Aveiro. For the evaluation of mecC gene it was obtained an overall prevalence of 0.009 (95% CI = 0005-0013). Despite the rare prevalence of this gene and absence of suspected strains, it is of utmost importance in clinical and epidemiological terms to screen this new form of methicillin-resistant Staphylococcus aureus. For the evaluation of global evidence of vancomycin “MIC creep”, our results do not suggest the presence of this phenomenon. The results obtained showed that mean values of vancomycin Minimum Inhibitory Concentration, of all methicillin-resistant Staphylococcus aureus isolates reported, were 1.19 mg/L and 1.20 mg/L determined by Etest and Broth Microdilution method, respectively. At the regional level, our results showed no evidence of “MIC creep” but described differences in methodologies applied to determine vancomycin Minimum Inhibitory Concentration. Either with the evaluation of the Minimum Inhibitory Concentration of vancomycin values or with research of the mecC gene in Staphylococcus aureus, this work highlights the need to better understand the resistance of nosocomial infections to antibiotics and to alert clinicians to the possibility of resistance to vancomycin scenario and the microbiology laboratories for the risk of new strains carrying the resistance gene.